A new American-lineage English?: Proportions of American variants in Japanese English. Issue 1 (2nd January 2021) - Borlongan, Ariane Macalinga
ABSTRACT: This article inquires into the proportions of putative American variants in diachronic data of Japanese English and, subsequently, comments on the direction this specific East Asian, Expanding Circle English is taking, particularly in relation to change broadly and Americanization specifically. As a whole, Japanese English has a very obvious preference for American variants. Although the proportions of American variants in Japanese English have declined from the 1960s to the 1990s, such a decline is not significant. Comparatively across Englishes, Japanese English also stands as such a heavily American-influenced English that it has even surpassed American and Philippine Englishes in its recorded use of American variants. Thus, from a variationist sociolinguistic and diachronic standpoint, it could be said that Japanese English is has very strong preference for American variants, almost to the point of appearing as an American-lineage English.